HOX transcription factors are potential targets and markers in malignant mesothelioma. Issue 1 (December 2016) - Morgan, Richard; Simpson, Guy; Gray, Sophie; Gillett, Cheryl; Tabi, Zsuzsanna; Spicer, James; Harrington, Kevin; Pandha, Hardev
Abstract Background TheHOX genes are a family of homeodomain-containing transcription factors that determine cellular identity during development and which are dys-regulated in some cancers. In this study we examined the expression and oncogenic function ofHOX genes in mesothelioma, a cancer arising from the pleura or peritoneum which is associated with exposure to asbestos. Methods We tested the sensitivity of the mesothelioma-derived lines MSTO-211H, NCI-H28, NCI-H2052, and NCI-H226 to HXR9, a peptide antagonist of HOX protein binding to its PBX co-factor. Apoptosis was measured using a FACS-based assay with Annexin, andHOX gene expression profiles were established using RT-QPCR on RNA extracted from cell lines and primary mesotheliomas. The in vivo efficacy of HXR9 was tested in a mouse MSTO-211H flank tumor xenograft model. Results We show thatHOX genes are significantly dysregulated in malignant mesothelioma. TargetingHOX genes with HXR9 caused apoptotic cell death in all of the mesothelioma-derived cell lines, and prevented the growth of mesothelioma tumors in a mouse xenograft model. Furthermore, the sensitivity of these lines to HXR9 correlated with the relative expression ofHOX genes that have either an oncogenic or tumor suppressive function in cancer. The analysis ofHOX expression in primary mesothelioma tumors indicated that these cells could also be sensitive to the disruption of HOX activity by HXR9, and that the expression ofHOXB4 is strongly associated with overall survival. Conclusion HOX genes are a potential therapeutic target in mesothelioma, andHOXB4 expression correlates with overall survival.